Immunization Status of Children with Acute Diarrhea Presenting to a Tertiary Care - Farhan Billoo, Irfan Karim, Asif Javeed, Roshaan Bashir, Nusrat Hussain, Riaz Ul Haq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Children less than 2 years of age must be fully vaccinated which may reduce the burden of life threatening diseases. Objective: The aim of this study was to find out the Immunization status of children with acute diarrhea presenting to a tertiary care hospital Materials and Method: The current cross sectional study was carried out at the department of Paediatrics Sheikh Zayed Hospital Rahim Yar Khan from October 2022 to March 2023 after taking permission from the ethical board of the institute. 416 children of both sexes, ages 0–2 years, who had severe diarrhea and had at least three loose stools daily for a period of not more than two weeks were enrolled . Data was obtained from each individual who visited the emergency room or OPD with severe diarrhea. Through EPI cards, the parents of these individuals were asked about the children's immunization status. The percentages and frequencies of each qualitative variable, including sex and immunization status (full, partial, or not immunized), were analyzed. Age and other quantitative factors were measured using mean + standard deviation. The male-to-female ratio was computed for gender. Tables and graphs were used to display the results. SPSS version 24 was used for data analysis. Results: A total of 416 children with acute gastroenteritis of both gender and different age groups (1-2 years) were examined in this study. Out of which male were 277 and female were 139. 1 to 2 years of children were enrolled in which the most prevalent age group was 5-8 months 206(49.5%). The immunization status revealed that 167 (40.1%) had completed their vaccinations, 84 (20.1%) had not fully completed, and 165 (39.5%) were not immunized. The distribution of immunization status by age reveals that 56 (40%) were fully vaccinated, 28 (20%) were partially vaccinated, and 56 (40%) were not immunized at or below 5 months of age. The distribution of individuals by sex showed that 56 (40.2%) female and 112 (40.4%) male had completed their vaccination. On the other hand, 56 (40.2%) of the children in the non-immunized group were female, and 109 (30.3%) were male. Conclusion: The current study concluded that only 40 % of the children of 1 -2 years of age were fully vaccinated and this immunization status is not satisfactory. It is necessary to raise public awareness and educate the public about the value of vaccinations. Keywords: Immunization; Children; Acute diarrhea.